2019
DOI: 10.1177/1066896919843337
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyomatous Hamartomas of the Oral Cavity: Clinicopathological and Immunohistochemical Features of 4 Cases and Literature Review

Abstract: Objective. To present 4 new cases of oral leiomyomatous hamartomas (OLH), describing its clinical, microscopical, and immunohistochemical features, and a literature review. Methods. The OLH cases were retrieved from the files of 2 Brazilian and 1 Peruvian oral pathology services. Clinical data were obtained from the pathology reports. Microscopical features were reviewed, and immunohistochemical reactions were performed. A review of the English-language literature about OLH was done. Results. The sample was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Four patients were at least 4 years of age, whereas one patient was 5 months old. 3,14,19 These cases similarly did not report lesion recurrence.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Four patients were at least 4 years of age, whereas one patient was 5 months old. 3,14,19 These cases similarly did not report lesion recurrence.…”
Section: Discussionmentioning
confidence: 60%
“…More recently, Sanchez‐Romero et al reported an additional four cases of oral leiomyomatous hamartomas with literature review through March 2019. Their work characterized 42 oral hamartomas by location, size, and morphology; however, diagnostic workup, treatment, and management recommendations remained vague 3 . Case reports have reported a variety diagnostic evaluations of lingual hamartomas, including magnetic resonance imaging (MRI), computed tomography (CT), neck ultrasonography, and thyroid uptake scans.…”
Section: Introductionmentioning
confidence: 99%
“…Per our literature review to date, there are a total of 28 cases of lingual leiomyomatous hamartomas, or smooth muscle-predominant hamartomas, reported in the literature, with 19 of them being on the dorsum of the tongue, as in our present case ( Table 1 ) [ 5 25 ]. Other locations of these hamartomatous lesions in the oral cavity include the anterior maxilla and the hard palate [ 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the oral hamartomas occurred at the tongue [33]. At least 50% leiomyomatous hamartoma were known to be present at birth and the most common age of diagnosis was under 12months [34]. The mass of oral hemartoma mostly are asymptomatic.…”
Section: Hamartomamentioning
confidence: 99%